The assessment of intellectualisation of the movement techniques teaching in terms of effective and pro-health training in young football players - Duda, H.; Mucha, D.; Ambrozy, T.; Omorczyk, J.; Dybinska, E.; Mucha, D. (Baltic Journal of Health and Physical Activity, 2016)
Background: Sporting success puts high requirements in terms of physical stress, it causes a major threat to an athlete`s health. Therefore, there is a need for effective training methods in order to reduce the number of contusions and sports injuries. For this purpose a method of intellectual training in the mastery of motor actions (playing technique) of young football players is recommended.